Aromatic C–H Addition to Ketones: The Effect of Directing Groups. Issue 28 (13th September 2013) - Zhang, Xi‐Sha; Zhu, Qi‐Lei; Luo, Fei‐Xian; Chen, Guihua; Wang, Xin; Shi, Zhang‐Jie
Abstract: The first example of the transition‐metal‐catalyzed direct intermolecular C–H bond addition to ketones was achieved by using a rhodium catalyst. A significant influence of the directing group on the reactivity was observed, and sterically more hindered directing groups could promote the reaction. In addition, intermolecular hydrogen bonding played a role in stabilizing the product. The substrate scope for the quinoline derivatives was very good. Abstract : The Rh III ‐catalyzed intermolecular nucleophilic addition of aromatic C–H bonds to ketones is reported. The steric hindrance of the directing group plays a vital role in promoting reactivity. A coordinating atom in the ketone is thought to stabilize the intermediate in addition to the product through coordination to the metal center and intramolecular hydrogen bonding, respectively. Cp* = C5 Me5, DCE = 1, 2‐dichloroethane.